The Brunei Malay Dilemma : Historical and Contemporary Challenges in Census Identity - Dg. Junaidah l, Awang Jambo; Mohamad Ikhram, Mohd Ridzuan; Noor Syakirah Zakaria, Zakaria; Nurulasyikin, Hassan; Nur Auni, Ugong; Mohd Waliuddin, Mohd Razali (HRMARS, 2024)
This article examines the controversy surrounding the identification of the Brunei Malay community in Sabah after the independence of Sabah. In this context, the discussion focuses on how the position of the Brunei Malay community changed in the census records of Sabahans before and after Sabah's independence. Based on the initial record of the implementation of the population census in North Borneo by the British North Borneo Chartered Company (BNBC) and the British colonial government from 1891 to 1960, this distinction in racial categorization is evident. From the first record of the population census in North Borneo in 1891 until the last record of the population census issued by the British colonial government, it was discovered that the Brunei Malay community stood alone as a "native." However, the recording in terms of the categorization of bumiputera in the Sabah census has undergone significant and inconsistent changes since Sabah's independence. Comparing census reports of the population before and after Sabah's independence revealed that the classification of Brunei Malays as the only bumiputera in the population census has changed to bumiputera lain-lain (others) category after Sabah's independence. Although the Brunei Malay community is the largest minority in Sabah, their political, economic, and social aspects are not regressive. Therefore, this article will attempt to explore and trace the polemic, issues, and challenges in promoting the change in the position of Brunei Malays to become a native bumiputera entity, as per the previous record so that they are no longer included in the other bumiputera category in the Sabah population census record.